Urban Stormwater Management with Rain Gardens – A Case Study of Kecskemét, Hungary - Hoyk, Edit; Csomós, György; Szórát, Krisztián; Farkas, Jenő Zsolt (Geographica Pannonica, 2025)
This research explores the potential benefits of rain gardens, a form of nature-based solutions (NbS) for urban stormwater management in Kecskemét, Hungary. An experimental rain garden was established using plants with varying drought tolerances to capture rainwater from a single-family house roof. This garden was monitored for a year to assess its rainwater retention capacity and observe plant development and survival. Concurrently, we identified areas within Kecskemét prone to flash floods from heavy rainfall, demarcating promising locations for rain garden conversion. Our primary goal was to identify applicable plant species and quantify how much rainfall could be retained in rain gardens. Our results show that drought-tolerant plants (e.g. Festuca amethystina, Festuca pallens glauca) perform better in the dry conditions typical of Kecskemét. Based on our calculation, the possible rainwater retention is about 1,500 m³, with 60 planned rain gardens. These findings suggest that the widespread urban application of rain gardens, as a nature-based solution, can significantly contribute to mitigating flash floods and enhancing urban resilience to extreme weather events.
Keywords: rain garden; stormwater; water retention; extreme precipitation; Hungary